(untitled) (Journal of the College of Basic Education, 2023)
Coherence is the second of seven criteria which are applied by (Bougrand) to prove the textual for a text; and this is achieved through semantic relations that can adjust among various concepts within the text, and it is far from the formal aspects of connecting. Semantic associations depend on among the meanings within the text, down to understand the speaker’s message (Nawawi’s Hadiths) considered to be the field of semantic suggestion of the reporting from him (May Allah bless him and his family) and in receiving from the recipients of the holy text, which preserved Hadith’s signs message which the prophet Mohammed (PBUH) throughout the time.